Organização e satisfação no contexto do teletrabalho - Tremblay, Diane-Gabrielle (2002)
This article results from a research on telework which was conducted with six public and private organizations. We also did a phone survey for which we have some 500 respondents, half of which are “salaried teleworkers”. After having presented a portrait of who does telework, we deal with issues such as the impacts of telework on work organization and working conditions, as well as the advantages and disadvantages that workers see in telework. We also address the issue of satisfaction among teleworkers, and conclude on the main dimensions to be addressed by organizations that want to implement telework. While the research wasnot carried out in Brazil, but in Canada, Brazilian firms have the same interest as Canadian firms in developing telework, that is reducing urban congestion, increasing their presence in different parts of the large national territory and ensuring the satisfaction of their workers to increase productivity and quality.